Sistem Pendukung Keputusan Pemberian Kredit Usaha Rakyat Menggunakan Metode Simple Additive Weighting Studi Kasus : Bank BRI Cabang Pondok Indah - Dion Ilham Saputra; Ari Syaripudin (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
People's business loans or KUR are loans that receive subsidized facilities from the government, one of which is KUR BRI or KUR BRI (KUR BRI 2021). The support system to determine the best alternative value that is worthy of receiving people's business credit uses the Simple Additive Weighting (SAW) method with predetermined criteria. The development tool used is Flowchart with PHP programming language with Laravel and MySQL database. The basic concept of the Simple Additive Weighting method is to find the weighted sum of the performance appraisals for each alternative on all attributes. The SAW method requires the process of normalizing the decision matrix to a scale that can be compared with all the existing rating alternatives. From the existing criteria, the calculation process for each criterion is carried out to obtain the best alternative results that are worthy of credit.